2018
DOI: 10.1111/cas.13584
|View full text |Cite
|
Sign up to set email alerts
|

Induction of chemokine (C‐C motif) ligand 5 by Epstein–Barr virus infection enhances tumor angiogenesis in nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is etiologically associated with Epstein–Barr virus (EBV) infection and is known to be highly vascularized. Previous studies have suggested that EBV oncoproteins contribute to NPC angiogenesis. However, the regulatory network of EBV in angiogenesis still remains elusive. Herein, we reveal a novel mechanism of EBV‐induced angiogenesis in NPC. First, we showed that EBV‐infected NPC cell lines generated larger tumors with more microvessels in mouse xenograft models. Subsequent prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…We hypothesize that a higher rate of tumor cell loss associated with larger tumor volume and poorer oxygen supply may account for this phenomenon. Furthermore, higher proliferation rates and favorable tumor angiogenesis associated with advanced N category and larger tumor volume may be another explanation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that a higher rate of tumor cell loss associated with larger tumor volume and poorer oxygen supply may account for this phenomenon. Furthermore, higher proliferation rates and favorable tumor angiogenesis associated with advanced N category and larger tumor volume may be another explanation …”
Section: Discussionmentioning
confidence: 99%
“…Tumor angiogenesis is associated with metastasis and may account for release of EBV DNA into circulation. A preclinical research revealed that EBV infection could promote the production of chemokine (C‐C motif) ligand 5, which increases vascular endothelial growth factor expression and NPC angiogenesis by interacting with the PI3K/AKT and hypoxia‐inducible factor‐1α pathways . It also has been found that level of plasma EBV DNA is also associated with tumor cell metabolic activity measured by PET/CT and circulating cytokines which may reflect the immune and inflammatory status of the body .…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was performed as previously described 44. Cells were lysed in RIPA lysis buffer containing protease inhibitors (Roche).…”
Section: Methodsmentioning
confidence: 99%
“…CCL5 may cause differentiation of cancer stem cells into endothelial cells as observed in the ovarian cancer model [ 103 ]. This chemokine is also induced by the Epstein–Barr virus (EBV) (human herpesvirus 4) in nasopharyngeal carcinoma cells, which leads to angiogenesis [ 104 ]. It may also indirectly cause lymphangiogenesis by increasing VEGF-C expression, as observed in chondrosarcoma cells [ 105 ].…”
Section: Ccr5 Ligandsmentioning
confidence: 99%